Succession of necrophagous entomofauna and life cycle of Calliphora vicina (Diptera: Calliphoridae) as the first colonizer species, using white pig (Sus scrofa) in Bogotá - CAMACHO-C., GINNA (Revista Colombiana de Entomología, 2005)
This it is the first succession study of cadaverous fauna in the sabana de Bogotá. The succession of cadaverous entomofauna and the approximation of the calculation of the postmortem interval (PMI) was determined using white pig (Sus scrofa) as a biomodel. During six months 3,497 individuals insect were collected. The most abundant families were Muscidae, Fannidae, Calliphoridae and Silphidae. The most abundant genera were Chloroprocta (Diptera: Calliphoridae), Fannia (Diptera: Fannidae), Muscina (Diptera: Muscidae), Coproica (Diptera: Sphaeroceridae), and Onthophagus (Coleoptera: Scarabaeidae), and the species Calliphora vicina (Robineau-Desvoidy) (Diptera: Calliphoridae), Cochliomyia macellaria (Fabricius) (Diptera: Calliphoridae), Lucilia sericata (Meigen) (Diptera: Calliphoridae) and Oxelytrum discicolle (Brullé) (Coleoptera: Silphidae). Five states of decomposition were differentiated: fresh (2 days), inflation (13 days), active decomposition (5 days), advanced decomposition (41 days) and dry remains (123 days). A table of the probability of appearance of the families was elaborated along each one of the days of sampling. Calliphora vicina was the first colonizer with a development time of 38 days. Growth and development curves were built adjusted to a statistical model for the larval stage. The effectiveness of the curves of growth and development of the succession of cadaverous fauna and of the probability table were demonstrated in the resolution of a forensic case.